PPE / PBT alloy material and preparation method thereof
By using composite toughening agents combined with olefin polymers and olefin acrylate polymers in PPE/PBT alloys, the problem of low impact strength of the alloy is solved, the impact strength and flame retardant properties of the material are improved, and the further improvement is achieved. Good compatibility and mechanical properties.
Patent Information
- Application Number
- CN202411548375.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-27
AI Technical Summary
The PPE/PBT alloy prepared by adding a compatible agent has a low impact strength.
The PPE/PBT alloy is modified by combining olefin polymers and olefin acrylate polymers as composite toughening agents. The elastic particles in the toughening agent tend to deform when subjected to impact force and absorb a large amount of energy, thereby improving the alloy. impact strength.
The impact strength of PPE/PBT alloy is significantly improved, and the flame retardant grade reaches UL-94 standard, improving the compatibility and mechanical properties of the material.
Smart Images

Figure BDA0005114410770000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer alloy material modification, and further relates to a PPE / PBT alloy material and a preparation method thereof. Background Art
[0002] PPE (polyphenylene ether, also referred to as PPO) is a non-crystalline thermoplastic resin with high mechanical strength and good heat resistance, low moisture absorption, good dimensional stability and other characteristics. However, one of the main drawbacks of PPE is that its glass transition temperature is high and processing is difficult. To overcome this drawback, PPE resin needs to be blended with other resins to make alloys.
[0003] In recent years, many researchers have done a lot of research on PPE / PA alloys, including capacity expansion, toughening, strengthening and commercialization, and have achieved good results and are being promoted. PPE and PA blends can not only improve the processing performance and solvent resistance of PPE, but also improve the heat resistance and dimensional stability of PA. However, the water absorption rate of PPE / PA alloy materials is relatively high, and large precision parts cannot be injection molded.
[0004] The PPE / PBT alloy prepared by blending PPE and PBT can maintain low water absorption, and the physical and mechanical properties do not change due to water absorption, while having the heat resistance, high impact strength and good solvent resistance of PPE / PA alloy. PPE is a non-crystalline resin, and PBT (polybutylene terephthalate) is a crystalline thermoplastic resin; the non-crystalline resin PPE has poor compatibility with the crystalline PBT resin, and the comprehensive performance of the alloy material after direct blending and modification is very unsatisfactory; therefore, the key to preparing PPE / PBT alloy is to improve the compatibility between the two phases.
[0005] At present, there are two methods to improve the compatibility between PPE and PBT. One method is to add reactive compatibilizers, such as epoxy coupling agents, styrene polymers containing epoxy or anhydride groups such as SMAH, styrene-glycidyl methacrylate (GMA) copolymers, etc., which are effective reactive compatibilizers for PPE / PBT alloys. Another method is to first chemically modify PPE to give it groups that can react with the PBT end groups, and then blend it with PBT. The groups that can react with the PBT end groups include carboxyl, amino, hydroxyl, and ester groups. Due to the different reactivity of these groups with PBT, the size of their compatibilization effect is: carboxyl>amino>hydroxyl>ester.
[0006] Although the above methods can improve the processing performance and mechanical properties of PPE / PBT alloys to a certain extent, they still have the disadvantages of unsatisfactory compatibility or high cost. In particular, the most obvious problem of preparing PPE / PBT alloys by adding compatibilizers is that the impact strength of the prepared PPE / PBT alloys is low. Summary of the invention
[0007] The technical problem solved by the invention is that the impact strength of the PPE / PBT alloy prepared by adding a compatibilizer is low.
[0008] The present invention selects olefin polymers and olefin acrylate polymers as composite toughening agents to modify PPE / PBT alloys; when the modified PPE / PBT alloy is subjected to impact force, elastic particles in the composite toughening agent are easily deformed and absorb a large amount of energy, thereby having high impact strength.
[0009] One of the objects of the present invention is to provide a PPE / PBT alloy material.
[0010] The PPE / PBT alloy material is prepared from raw materials including the following components:
[0011] Taking the total amount of raw materials as 100wt%, the components and their contents are as follows:
[0012] PPE resin 20-80wt%, preferably 30-70wt%;
[0013] PBT resin 10-80wt%, preferably 20-70wt%;
[0014] Compatibilizer 0.5-10wt%, preferably 2-7wt%;
[0015] Composite toughening agent 1-10wt%, preferably 3-7wt%;
[0016] Antioxidant 0.1-5wt%, preferably 0.2-2wt%;
[0017] Stabilizer 0.1-5wt%, preferably 0.2-2wt%;
[0018] The composite toughening agent is composed of two or more toughening agents.
[0019] The viscosity of the PPE resin can be selected within a wide range, and those skilled in the art can select according to actual conditions. As a preferred embodiment, the viscosity of the PPE resin is 0.30 dl / g to 0.52 dl / g, and more preferably 0.35 dl / g to 0.45 dl / g.
[0020] The viscosity of the PBT resin can be selected within a wide range, and those skilled in the art can select it according to actual conditions. As a preferred embodiment, the viscosity of the PBT resin is 0.68 dl / g to 1.30 dl / g, and more preferably 0.80 dl / g to 1.20 dl / g.
[0021] The compatibilizer can be selected from any one or more commonly used compatibilizers in the art, and those skilled in the art can select according to actual conditions. As a preferred embodiment, the compatibilizer is selected from one or more of maleic anhydride grafted polystyrene, maleic anhydride grafted SEBS, maleic anhydride grafted PPE, maleic anhydride grafted ABS, maleic anhydride grafted SBS, and ASA with epoxy functional groups.
[0022] The SEBS in maleic anhydride grafted SEBS is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenating polybutadiene as the middle elastic block;
[0023] The ABS in maleic anhydride grafted ABS is a terpolymer of acrylonitrile, butadiene, and styrene;
[0024] The SBS in maleic anhydride grafted SBS is a triblock copolymer with styrene and butadiene as monomers;
[0025] The ASA in the ASA with epoxy functional group is a ternary polymer formed by the polymerization of acrylonitrile (Acrylonitile), styrene (Styrene), and acrylic rubber (Acrylate).
[0026] The composite toughening agent is composed of toughening agent A and toughening agent B in a weight ratio of (1-5):1, preferably (2-4):1; specifically, the weight ratio of toughening agent A to toughening agent B can be 3:1.
[0027] The toughening agent A is an olefin polymer, and the molar content of the repeating structural units derived from olefins in the olefin polymer is 60% to 100%, preferably 70% to 95%; preferably, the toughening agent A is an olefin polymer grafted with maleic anhydride;
[0028] The toughening agent B is an olefin acrylate polymer.
[0029] Compared with using toughener A or toughener B alone, the mechanical properties of PPE / PBT alloy, including tensile strength, flexural strength and notched / unnotched strength, are significantly improved after the two are compounded.
[0030] The toughener A and toughener B both contain repeating structural units derived from olefins (olefin structures). Toughener A and toughener B are selected for compounding, and toughener A contains polar maleic anhydride side groups, which can improve the bonding between polar and non-polar materials and have a certain compatibility with PPE; toughener B contains "acrylate", which is affected by the end carboxyl group and has good compatibility with polar PBT, and can be used to toughen and modify PBT; toughener A and toughener B both contain similar olefin structures, so that toughener A and toughener B are more evenly dispersed between PPE and PBT after compounding, playing a "bridge" role; when the PPE / PBT alloy after blending and modification is subjected to impact force, its olefin long chain structure similar to the elastic structure of rubber is easy to deform, absorbs a large amount of energy, and inhibits crack propagation; thereby improving the toughness of the PPE / PBT alloy, so that the modified PPE / PBT alloy has strong impact resistance.
[0031] The olefin polymer can be selected from a wide range, and those skilled in the art can select it according to the actual situation. As a preferred embodiment, the MFR of the olefin polymer is 0.1 to 20 g / 10 min, preferably 0.5 to 6 g / 10 min; its number average molecular weight is 1×10 4 ~3×10 5 g / mol, preferably 2×10 4 ~1.5×10 5 g / mol; its Mooney viscosity is 3 to 37, preferably 5 to 35. As a preferred embodiment, the olefin polymer is selected from one or more of polyethylene, ethylene-octene copolymer, maleic anhydride grafted polyethylene, and maleic anhydride grafted ethylene-octene copolymer. That is, the toughening agent A is selected from one or more of polyethylene, ethylene-octene copolymer, maleic anhydride grafted polyethylene, and maleic anhydride grafted ethylene-octene copolymer.
[0032] The olefin acrylate polymer can be selected from a wide range, and those skilled in the art can select it according to the actual situation. As a preferred embodiment, the MFR of the acrylate polymer is 0.1 to 20 g / 10 min, preferably 0.5 to 6 g / 10 min; its number average molecular weight is 1×10 4 ~3×10 5 g / mol, preferably 2×10 4 ~1.5×10 5 g / mol; its Mooney viscosity is 3 to 37, preferably 5 to 35. As a preferred embodiment, the olefin acrylate polymer is selected from one or more of ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer or ethylene-butyl acrylate copolymer. That is, the toughening agent B is selected from one or more of ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer or ethylene-butyl acrylate copolymer.
[0033] As a preferred solution, the MFR of the composite toughening agent is 0.1 to 20 g / 10 min, preferably 0.5 to 6 g / 10 min.
[0034] The antioxidant may be selected from any one or more antioxidants commonly used in the art, and those skilled in the art may select according to actual conditions. As a preferred embodiment, the antioxidant is selected from one or more of hindered phenol antioxidants and phosphite antioxidants.
[0035] The stabilizer can be selected from any one or more stabilizers commonly used in the art, and those skilled in the art can select according to actual conditions. As a preferred embodiment, the stabilizer is selected from one or more of metal oxides and metal sulfides.
[0036] The PPE / PBT alloy material may also be added with other functional additives commonly used in the art, and those skilled in the art may add them according to actual conditions, and the amount added is a conventional amount. For example, the raw materials of the PPE / PBT alloy material also include a flame retardant; based on the total amount of raw materials as 100%, the flame retardant is 1 to 10 wt%, preferably 3 to 7 wt%. After adding the flame retardant, the PPE / PBT alloy material has flame retardant properties.
[0037] The flame retardant can be selected from any one or more commonly used flame retardants in the art, and those skilled in the art can select according to actual conditions. As a preferred embodiment, the flame retardant is selected from one or more organic phosphates, in which case the flame retardant grade of the PBT / PET alloy material can reach the UL-94 standard; in addition, when the organic phosphates and PPE resins are co-blended and extruded, the interaction between polymer molecular chains is weakened, and the flexibility and plasticity of the molecular chains are enhanced, thereby reducing the processing temperature of the PPE resin.
[0038] The second object of the present invention is to provide a method for preparing the PPE / PBT alloy material described in the first object of the present invention.
[0039] The preparation method of the PPE / PBT alloy material comprises:
[0040] (1) Treatment of PPE resin: PPE resin and stabilizer, optionally flame retardant, are mixed, extruded and pelletized; the extrusion temperature is 260-300° C., preferably 270-290° C.;
[0041] (2) Treatment of toughening agent: after two or more toughening agents are uniformly mixed, they are extruded and granulated; the extrusion temperature is 90-190°C, preferably 110-150°C;
[0042] (3) mixing the treated PPE resin, the treated toughening agent and other raw materials uniformly, extruding and granulating; the extrusion temperature is 220-290° C., preferably 255-270° C.;
[0043] Preferably, steps (1), (2) and (3) can all be carried out by extrusion granulation using a twin-screw extruder with a screw speed of 200-350 rpm.
[0044] In step (1), the processing temperature of the treated PPE resin is lowered to a certain extent, approaching the processing temperature of the PBT resin, so that the two can achieve better thermodynamic compatibility.
[0045] In step (2), when the composite toughening agent is composed of toughening agent A and toughening agent B, the toughening agent is treated by mixing toughening agent A and toughening agent B uniformly, and then extruding and granulating. The treated toughening agent can not only improve the toughness of the alloy material, but also improve the compatibility of the alloy material by utilizing its respective structure.
[0046] In step (3), other raw materials include PBT resin, compatibilizer and antioxidant.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] The PPE / PBT alloy material provided by the present invention not only retains the relatively high heat deformation temperature of the PPE resin part, but also improves the compatibility of the two materials. The mechanical properties of the material, especially the impact strength, are improved, and the flame retardant grade reaches the UL-94 standard. DETAILED DESCRIPTION
[0049] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0050] The present invention first describes the raw materials for preparing the PPE / PBT alloy material:
[0051] The present invention has no special limitation on the sources of the raw materials for preparation. Unless otherwise specified, the raw materials used are all commercially available products.
[0052] The PPE resin is produced by Ruicheng Branch of Nantong Xingchen Synthetic Materials Co., Ltd., model number is LXR040;
[0053] PBT resin was produced by Sinopec Yizheng Chemical Fiber Co., Ltd., model number GX121;
[0054] The flame retardant PX-220 is a polyaryl phosphate produced by Zhejiang Wansheng Co., Ltd., with the brand name PX-220;
[0055] Toughening agent KT-915 is maleic anhydride grafted ethylene-octene copolymer produced by Shenyang Ketong Plastic Co., Ltd., with the brand name KT-915;
[0056] Toughener 1125 is ethylene-methyl acrylate produced by DuPont, USA, with the brand name AC1125;
[0057] Toughening agent 3135 is ethylene-butyl acrylate produced by DuPont in the United States, with the brand name AC3135
[0058] The compatibilizer SMA-700 is maleic anhydride grafted polystyrene produced by Shanghai Huawen Electronic New Materials Co., Ltd., with the brand name SMA-700;
[0059] Antioxidant 1010 comes from Gu'an Huawei Additive Technology Co., Ltd., brand name HHZ-1010;
[0060] Antioxidant 168 comes from Gu'an Huawei Additive Technology Co., Ltd., brand name HHP-168;
[0061] The stabilizer zinc oxide comes from Huludao Zinc Plant in Liaoning;
[0062] The stabilizer zinc sulfide comes from Sahaliben, Germany, with the brand name HD-S.
[0063] Example 1
[0064] Prepare raw materials: the raw materials and their weight percentage are: 59% PPE resin, 5% flame retardant PX-220, 0.25% stabilizer zinc oxide, 0.25% stabilizer zinc sulfide, 3.75% toughening agent KT-915, 1.25% toughening agent 1125, 25% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, and 0.25% antioxidant 168.
[0065] The preparation method is as follows:
[0066] (1) Treatment of PPE resin: PPE resin was mixed with flame retardant PX-220, stabilizer zinc oxide and stabilizer zinc sulfide in percentage and then added to a co-rotating twin-screw extruder from a main feed port. The extruder had a diameter of Φ30 mm and an aspect ratio of 40:1. The process parameters of the extruder were as follows: zone 1 temperature 275°C, zone 2 temperature 275°C, zone 3 temperature 280°C, zone 4 temperature 280°C, zone 5 temperature 278°C, zone 6 temperature 278°C, zone 7 temperature 275°C, zone 8 temperature 275°C, zone 9 temperature 275°C, zone 10 temperature 270°C, and the screw speed was 250 rpm. After extrusion, the material was cooled in a water bath, air-dried and pelletized for later use.
[0067] (2) Treatment of toughening agent: Toughening agent KT-915 and toughening agent AC1125 were mixed uniformly according to percentage and then added into a co-rotating twin-screw extruder from the main feeding port. The diameter of the extruder was Φ30 mm and the aspect ratio was 40:1. The process parameters of the extruder were as follows: temperature of zone 1: 115°C, temperature of zone 2: 115°C, temperature of zone 3: 120°C, temperature of zone 4: 120°C, temperature of zone 5: 120°C, temperature of zone 6: 120°C, temperature of zone 7: 120°C, temperature of zone 8: 115°C, temperature of zone 9: 115°C, temperature of zone 10: 110°C, and the screw speed was 250rpm. After extrusion, the material was cooled in a water bath, air-dried, granulated, and set aside.
[0068] (3) Preparation of alloy material: PBT resin was dried in an oven at 120°C for 4 h, and after cooling, it was mixed with treated PPE resin, treated toughening agent, compatibilizer SMA-700, antioxidant 1010 and antioxidant 168, and after mixing evenly, it was added to a co-rotating twin-screw extruder from the main feeding port. The extruder diameter was Φ30 mm and the aspect ratio was 40:1. The process parameters of the extruder were as follows: zone 1 temperature 265°C, zone 2 temperature 265°C, zone 3 temperature 270°C, zone 4 temperature 270°C, zone 5 temperature 265°C, zone 6 temperature 260°C, zone 7 temperature 260°C, zone 8 temperature 260°C, zone 9 temperature 255°C, zone 10 temperature 255°C, and the screw speed was 250rpm. After extrusion, the material was cooled in a water bath, air-dried and pelletized to obtain a PPE / PBT alloy material.
[0069] Example 2
[0070] Prepare raw materials: the raw materials and their weight percentage are: 50% PPE resin, 5% flame retardant PX-220, 0.25% stabilizer zinc oxide, 0.25% stabilizer zinc sulfide, 3.75% toughening agent KT-915, 1.25% toughening agent 1125, 34% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, and 0.25% antioxidant 168.
[0071] The PPE / PBT alloy material was prepared according to the method of Example 1.
[0072] Example 3
[0073] Prepare raw materials: the raw materials and their weight percentage are: 59% PPE resin, 5% flame retardant PX-220, 0.25% stabilizer zinc oxide, 0.25% stabilizer zinc sulfide, 7.5% toughening agent KT-915, 2.5% toughening agent 1125, 20% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, and 0.25% antioxidant 168.
[0074] The PPE / PBT alloy material was prepared according to the method of Example 1.
[0075] Example 4
[0076] Prepare raw materials: the raw materials and their weight percentage are: 54% PPE resin, 5% flame retardant PX-220, 0.25% stabilizer zinc oxide, 0.25% stabilizer zinc sulfide, 7.5% toughening agent KT-915, 2.5% toughening agent 1125, 25% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, and 0.25% antioxidant 168.
[0077] The PPE / PBT alloy material was prepared according to the method of Example 1.
[0078] Example 5
[0079] Prepare raw materials: the raw materials and their weight percentage are: 59% PPE resin, 5% flame retardant PX-220, 0.25% stabilizer zinc oxide, 0.25% stabilizer zinc sulfide, 3.75% toughening agent KT-915, 1.25% toughening agent 3135, 25% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, and 0.25% antioxidant 168.
[0080] The PPE / PBT alloy material was prepared according to the method of Example 1.
[0081] Example 6
[0082] Prepare the raw materials according to Example 1.
[0083] The preparation method is as follows:
[0084] Preparation of alloy material: PBT resin is placed in an oven at 120°C and dried for 4 hours. After cooling, it is mixed with PPE resin, toughening agent, compatibilizer SMA-700, antioxidant 1010, antioxidant 168, stabilizer zinc oxide and zinc sulfide. After mixing evenly, it is added to a co-rotating twin-screw extruder from the main feeding port. The extruder diameter is Φ30 mm and the aspect ratio is 40:1. The process parameters of the extruder are as follows: zone 1 temperature 275°C, zone 2 temperature 275°C, zone 3 temperature 280°C, zone 4 temperature 280°C, zone 5 temperature 278°C, zone 6 temperature 278°C, zone 7 temperature 275°C, zone 8 temperature 275°C, zone 9 temperature 275°C, zone 10 temperature 270°C, and the screw speed is 250rpm. After extrusion, the material is cooled in a water bath, air-dried and pelletized to obtain a PPE / PBT alloy material.
[0085] Comparative Example 1
[0086] Prepare raw materials: the raw materials and their weight percentage are: 65.8% PPE resin, 28.2% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, 0.25% antioxidant 168, 0.25% stabilizer zinc sulfide, and 0.2%5 stabilizer zinc oxide.
[0087] The preparation method is as follows: PBT resin is placed in an oven at 120°C and dried for 4 hours, and after cooling, it is mixed with PPE resin, compatibilizer SMA-700, antioxidant 1010, antioxidant 168, stabilizer zinc oxide and zinc sulfide, and after mixing evenly, it is added to a co-rotating twin-screw extruder from a main feeding port, the extruder diameter is Φ30 mm, and the aspect ratio is 40:1; the process parameters of the extruder are as follows: zone 1 temperature 275°C, zone 2 temperature 275°C, zone 3 temperature 280°C, zone 4 temperature 280°C, zone 5 temperature 278°C, zone 6 temperature 278°C, zone 7 temperature 275°C, zone 8 temperature 275°C, zone 9 temperature 275°C, zone 10 temperature 270°C, and the screw speed is 250rpm; after extrusion, the material is cooled in a water bath, air-dried and pelletized to obtain a PPE / PBT alloy material.
[0088] Comparative Example 2
[0089] Prepare raw materials: the raw materials and their weight percentage are: 59% PPE resin, 5% flame retardant PX-220, 0.25% stabilizer zinc oxide, 0.25% stabilizer zinc sulfide, 5.0% toughening agent KT-915, 25% PBT resin, 5% compatibilizer SMA-700, 0.25% antioxidant 1010, and 0.25% antioxidant 168.
[0090] The preparation method is as follows:
[0091] Preparation of alloy material: PBT resin is placed in an oven at 120°C and dried for 4 hours. After cooling, it is mixed with PPE resin, toughening agent, compatibilizer SMA-700, antioxidant 1010, antioxidant 168, stabilizer zinc oxide and zinc sulfide. After mixing evenly, it is added to a co-rotating twin-screw extruder from the main feeding port. The extruder diameter is Φ30 mm and the aspect ratio is 40:1. The process parameters of the extruder are as follows: zone 1 temperature 275°C, zone 2 temperature 275°C, zone 3 temperature 280°C, zone 4 temperature 280°C, zone 5 temperature 278°C, zone 6 temperature 278°C, zone 7 temperature 275°C, zone 8 temperature 275°C, zone 9 temperature 275°C, zone 10 temperature 270°C, and the screw speed is 250rpm. After extrusion, the material is cooled in a water bath, air-dried and pelletized to obtain a PPE / PBT alloy material.
[0092] Performance Testing
[0093] The PPE / PBT alloy materials prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were dried in an oven at 120° C. for 3 hours and then injection molded into standard test specimens to test their mechanical properties and combustion properties. The performance evaluation method and implementation standards are as follows:
[0094] The tensile strength is tested according to ISO527 standard;
[0095] The bending strength is tested according to ISO178 standard;
[0096] Impact strength is tested according to ISO179 standard;
[0097] Heat deformation temperature is tested according to ISO75, load 1.8MPa:
[0098] The flame retardant properties are tested according to UL-94 standard.
[0099] The test results are shown in Table 1.
[0100] Table 1 Performance test results of PPE / PBT alloy materials prepared in various embodiments and comparative examples
[0101]
[0102] In Table 1, “flame retardant / 3.2 mm” means that the thickness of the sample is 3.2 mm, “V-0” means that the flame retardant grade is UL94 V-0, and “HB” means that the flame retardant grade is UL94 HB.
[0103] Table 1 shows that compared with Comparative Example 1, the "tensile strength" of Examples 1-6 increased by 44% to 104%, the "flexural strength" increased by 65% to 80%, the "notched impact strength" increased by 200% to 866%, and the "unnotched impact strength" increased by 145% to 364%. Compared with Comparative Example 1, the difference between Examples 1-6 is that the composite toughening agent described in the present invention is added. It can be seen that adding the composite toughening agent to the raw material can not only significantly improve the tensile strength and flexural strength of the PE / PBT alloy material, but also significantly improve the notched impact strength and unnotched impact strength of the PPE / PBT alloy material.
[0104] Table 1 shows that compared with Comparative Example 2, the "tensile strength" of Examples 1-6 increased by 11% to 45%, the "flexural strength" increased by 3% to 12%, the "notched impact strength" increased by 125% to 625%, and the "non-notched impact strength" increased by 59% to 200%. The raw materials of Comparative Example 2 contain only one toughening agent, while the raw materials of Examples 1-6 contain a composite toughening agent compounded from two toughening agents; the difference between the two is only that Comparative Example 2 uses a single toughening agent, while Examples 1-6 use the composite toughening agent of the present invention. It can be seen that, compared with the single toughening agent of Comparative Example 2, the composite toughening agent of the present invention can further improve the tensile strength, flexural strength, notched impact strength and non-notched impact strength of the PPE / PBT alloy material; especially the improvement of notched impact strength and non-notched impact strength is more obvious.
[0105] Table 1 shows that, compared with Example 6, the "notched impact strength" of Example 1 is increased by 80%, the "unnotched impact strength" is increased by 52%, the heat deformation temperature is increased by 5°, and the processing temperature of step (3) is reduced by 10-15°C. The raw materials of Example 1 and Example 6 are exactly the same, and the only difference between Example 1 and Example 6 is that Example 1 adds the steps of "treating PPE resin" and "treating toughening agent". It can be seen that the steps of "treating PPE resin" and "treating toughening agent" can significantly reduce the processing temperature of PPE / PBT alloy materials, and can further improve the notched impact strength and unnotched impact strength of PPE / PBT alloy materials under the condition of reducing the processing temperature.
[0106] It can be seen from the performance test results of the above embodiments and comparative examples that (1) the addition of the composite toughening agent can improve the impact strength of the material with a small loss of heat deformation temperature; (2) after the addition of the flame retardant, the flame retardant properties of the alloy material are improved; (3) the use of PPE resin and toughening agent pretreatment can significantly improve the impact strength of the alloy material.
Claims
1. A PPE / PBT alloy material, characterized in that: The PPE / PBT alloy material is prepared from raw materials including the following components; Taking the total amount of raw materials as 100wt%, the components and their contents are as follows: PPE resin 20-80wt%, preferably 30-70wt%; PBT resin 10-80wt%, preferably 20-70wt%; Compatibilizer 0.5-10wt%, preferably 2-7wt%; Composite toughening agent 1-10wt%, preferably 3-7wt%; Antioxidant 0.1-5wt%, preferably 0.2-2wt%; Stabilizer 0.1-5wt%, preferably 0.2-2wt%; The composite toughening agent is composed of two or more toughening agents.
2. The PPE / PBT alloy material according to claim 1, characterized in that: The viscosity of the PPE resin is 0.30 dl / g to 0.52 dl / g, preferably 0.35 dl / g to 0.45 dl / g; or / and, The viscosity of the PBT resin is 0.68 dl / g to 1.30 dl / g, and preferably 0.80 dl / g to 1.20 dl / g.
3. The PPE / PBT alloy material according to claim 1, characterized in that: The compatibilizer is selected from at least one of maleic anhydride grafted polystyrene, maleic anhydride grafted SEBS, maleic anhydride grafted PPE, maleic anhydride grafted ABS, maleic anhydride grafted SBS, and ASA with epoxy functional group.
4. The PPE / PBT alloy material according to claim 1, characterized in that: The composite toughening agent is composed of toughening agent A and toughening agent B in a weight ratio of (1-5):1, preferably (2-4):1; The toughening agent A is an olefin polymer, and the molar content of the repeating structural units derived from olefins in the olefin polymer is 60% to 100%, preferably 70% to 95%; preferably, the toughening agent A is an olefin polymer grafted with maleic anhydride; The toughening agent B is an olefin acrylate polymer.
5. The PPE / PBT alloy material according to claim 4, characterized in that: The olefin polymer is selected from one or more of polyethylene, ethylene-octene copolymer, maleic anhydride grafted polyethylene, and maleic anhydride grafted ethylene-octene copolymer; or / and, The olefin acrylic acid ester polymer is selected from at least one of ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer and ethylene-butyl acrylate copolymer.
6. The PPE / PBT alloy material according to claim 4, characterized in that: The MFR of the olefin polymer is 0.1 to 20 g / 10 min, preferably 0.5 to 6 g / 10 min; or / and, The MFR of the olefin acrylic ester polymer is 0.1 to 20 g / 10 min, preferably 0.5 to 6 g / 10 min.
7. The PPE / PBT alloy material according to claim 1, characterized in that: The antioxidant is selected from at least one of hindered phenol antioxidants and phosphite antioxidants.
8. The PPE / PBT alloy material according to claim 1, characterized in that: The stabilizer is selected from at least one of metal oxides and metal sulfides.
9. The PPE / PBT alloy material according to claim 1, characterized in that: Based on 100% of the total amount of raw materials, the raw materials further include 1 to 10 wt%, preferably 3 to 7 wt% of flame retardant; Preferably, the flame retardant is selected from one or more organic phosphates.
10. A method for preparing the PPE / PBT alloy material according to any one of claims 1 to 9, comprising: (1) Treatment of PPE resin: PPE resin and stabilizer, optionally flame retardant, are mixed, extruded and pelletized; The extrusion temperature is 260-300°C, preferably 270-290°C; (2) Treatment of toughening agent: after two or more toughening agents are uniformly mixed, they are extruded and granulated; the extrusion temperature is 90-190°C, preferably 110-150°C; (3) mixing the treated PPE resin, the treated toughening agent and other raw materials uniformly, extruding and granulating; the extrusion temperature is 220-290° C., preferably 255-270° C.; Preferably, steps (1), (2) and (3) are all carried out by extrusion granulation using a twin-screw extruder, with the screw speed being 200-350 rpm.
